pls answer it fast!!
Attachments:
![](https://hi-static.z-dn.net/files/d88/ac58d0d8d372e87efcf8976a2f700086.jpg)
Answers
Answered by
2
Let : x = 5 + 2√6.
Then : x = 3 + 2 + 2√((3)(2))
∴ x = (√3)² + (√2)² + 2(√3)(√2) = (√3 + √2)²
∴ √x = √3 + √2
∴ 1/(√x) = 1/(√3 + √2) = √3 - √2
∴ (√x) + (1/√x) = 2√3 ...Answer
Happy to help you dear :)
Then : x = 3 + 2 + 2√((3)(2))
∴ x = (√3)² + (√2)² + 2(√3)(√2) = (√3 + √2)²
∴ √x = √3 + √2
∴ 1/(√x) = 1/(√3 + √2) = √3 - √2
∴ (√x) + (1/√x) = 2√3 ...Answer
Happy to help you dear :)
Answered by
1
Answer:
.,.mark as brainliest
Step-by-step explanation:
........................
Similar questions